Sleep Increases Amplitude of Mu-Beta Oscillations during Motor Sequence Memory Consolidation - Albouy, G.; Lecaignard, F.; Delpuech, C.; Aguera, P.E.; Luppi, P.H.; Nicolas, A.; Maquet, P.; Bertrand, O. (NeuroImage (Orlando, Fla.), 2009)
Results Non-parametric statistical analyses revealed that the main effect of learning during training in all subjects was significant over right, medial and left central sensors and in frequency bands ranging from 10 to 15 Hz (mu rhythm) and from 20 to 25 Hz (beta rhythm).